PERLINDUNGAN TERHADAP KORBAN PELANGGARAN HAK ASASI MANUSIA (HAM) BERAT DI KOREA UTARA MENURUT HUKUM INTERNASIONAL - Nella Octaviany Siregar; Chairul Bariah; Abdul Rahman (Journal of USU International Law, 2014)
Abstract: Human Rights are basic rights bestowed by God on human beings, are universal to be protected, respected, maintained, and should not be ignored, reduced or taken away by anyone. It is therefore the responsibility of the State as well as collateral for enforcement against violations of human rights principles. The UN as an international organization in its charter has been put respect and appreciation for human rights into the Charter that dsebut The Universal Declaration of Human Rights were adopted unanimously by the General Assembly of the United Nations General Assembly on December 10, 1948. Human rights violations in North Korea should have been the responsibility of the State concerned, and also it is a shared responsibility of the international community. North Korea as one of the countries with the worst human rights records. North Koreans have been referred to as the "most brutalized people in the world", due to the severe restrictions placed on the top of their political and economic freedoms. The North Korean government has committed human rights violations in the form of crimes against humanity against the civilian population, so in this case the UN acts as a protective shield against the civilian population, so that the perpetrators can not act arbitrarily in treating civilian population. Keyword: Human Rights, North Korea